Three essays in industrial organization - Işık, Mehtap. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
In the first chapter of the thesis, we consider the formation of networks over which a public good is produced (as opposed to considering given and fixed network structures). We identify that the multiplicity of equilibria of effort levels that are exerted in provision of public good on a given and fixed network structure differentiates the problem of formation of these networks from the existing literature. We suggest some stability definitions for these kinds of networks. In the second chapter, we consider the problem of dealing with piracy in a monopolistic digital market in which piracy exists in the form of end-user copying and commercial reproduction. We find that the governmental protection against commercial piracy is not socially optimal due to end-user copying. Moreover, when the monopolist differentiates its product across quality, it can cover the most of its profit losses by deterring piracy. In the third chapter, we formalize the discrete type space version of the corruption problem, which is identi ed by Koray and Saglam (2005a) in Baron and Myerson (1982) model of monopoly regulation. We propose a solution to the problem by using the framework driven by the Myerson (1979) for incentive compatible bargaining games. We also implement a simulation to gain a quantitative insight on the economic effects of the corruption bargaining game.
Keywords: Industrial organization.